2014
DOI: 10.1016/j.sleep.2014.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Is it time for bed? Short sleep duration increases risk of obesity in Mexican American children

Abstract: Objective Cross-sectional studies show that sleep is related to childhood obesity. We aimed to examine the longitudinal impact of sleep on obesity risk in Mexican American children. Design and Methods We evaluated 229 Mexican American 8–10-year-olds and their mothers at baseline and 12- and 24-month follow-ups. Sleep duration and anthropometrics were collected. Age- and gender-specific BMI z-scores (BMIz) were calculated based on Centers for Disease Control and Prevention guidelines. Sleep duration was estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 35 publications
2
27
0
3
Order By: Relevance
“…For example, in adults, decreased sleep duration is associated with an increased risk of obesity [26], and such an association is seen in Mexican Americans, but not in Cuban Americans or Puerto Ricans [27]. This association has also been described in Mexican-American children [28]. In our study, we aimed to test the hypothesis that there are ethnic differences in parent-reported sleep duration in a community-based cohort of Hispanic and Caucasian children.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in adults, decreased sleep duration is associated with an increased risk of obesity [26], and such an association is seen in Mexican Americans, but not in Cuban Americans or Puerto Ricans [27]. This association has also been described in Mexican-American children [28]. In our study, we aimed to test the hypothesis that there are ethnic differences in parent-reported sleep duration in a community-based cohort of Hispanic and Caucasian children.…”
Section: Introductionmentioning
confidence: 99%
“…Latino children suffer the highest obesity rates in the country and are at increased risk for lifelong metabolic illness [1]. At least one other study has shown that Mexican American children with shorter sleep duration are more likely to increase weight status over time [23]. Hence it seems important to target sleep in childhood obesity interventions in these communities.…”
Section: Discussionmentioning
confidence: 99%
“…Underserved populations stand to benefit from health interventions that target modifiable factors. Disparities in lifestyle variables like diet, activity and sleep have been documented between ethnic groups highlighting the importance of culturally appropriate approaches [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study conducted among 229 Mexican American 8-10-year-olds and concluded that children who slept less were more likely to have a higher BMI Z-Score [35]. A cohort study done in Japan observed positive relationship between decreased sleeping hours and obesity after adjusting for potential confounding factors [36].…”
Section: Sleeping Hoursmentioning
confidence: 99%